Development of the standard reference plane for the Heidelberg retina tomograph - Burk, Reinhard; Vihanninjoki, Kyösti; Bartke, Thomas; Tuulonen, Anja; Airaksinen, P. Juhani; Völcker, Hans Eberhard; König, Jochem (Graefe's archive for clinical and experimental ophthalmology, 2000)
Background: Topometry of the optic disc is the quantitative assessment of the structure of the optic nerve head by means of three- dimensional parameters. The parameter values depend on definitions of intraocular reference planes. Purpose: To describe the development of intraocular reference planes in laser scanning tomography for the Heidelberg Retina Tomograph (HRT) using image intrinsic data with a fixed offset reference plane (320 µm) and to present a contour-line-based ”flexible” standard reference plane (”SRP”) for calculation of intrapapillary stereometric parameters taking the interindividual variability of optic disc topography into account.Methods: Ten-degree triple images were obtained by laser scanning tomography from 99 glaucoma eyes and 180 normal eyes. The images were evaluated to assess the variability of height measurements of an optic disc border contour-line segment (6° width) corresponding to the site of the papillo-macular bundle as indicated by the average optic disc surface inclination angle. Results: The average optic disc surface inclination angle was -7°±3° below the horizontal meridian (0°). The 6° wide contour-line segment for the SRP was chosen according to the average surface inclination angle (-10° to -4°). The reproducibility of the SRP-segment height measurements was 16.0±10.8 µm for normal eyes and 23.4±18.0 µm for glaucoma eyes. To ensure that the automatic reference level determination for intrapapillary parameters remained below the disc border height, we defined the SRP level at a 50 µm offset (>2 SD of average segment height reproducibility in glaucoma) added to the individual height position of the 6° contour line segment. Conclusion: The flexible standard reference plane allows for automatic determination of intrapapillary variables once a disc border contour line is interactively defined. In contrast to a fixed offset reference plane (e.g. 320 µm below the mean retina height), the interindividual variability of optic disc topography (oblique insertion, glaucomatous surface flattening) is respected at the cost of the need for an accurate optic disc border outline.
Gesehen am 27.06.2022